Neighborhood Effects and Individual Unemployment - Thomas K. Bauer; Michael Fertig; Matthias Vorell (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
Using a unique dataset for Germany that links individual longitudinal data from the GSOEP to regional data from the federal employment agency and data of real estate prices, we evaluate the impact of neighborhood unemployment on individual employment propects. The panel setup and richness of the data allows us to overcome some of the identifi cation problems which are present in this strand of literature. The empirical results indicate that there is a signifi cant negative impact of neighborhood unemployment on the individual employment probability. – – Im Rahmen des SOEP Neighborhood Projekts wurden dem GSOEP prozessproduzierte Daten der Bundesagentur für Arbeit und Immobilienpreisdaten zugespielt. Mithilfe dieses Datensatzes identifizieren wir den Einfluss von Nachbarschaftsarbeitslosigkeit auf die individuelle Beschäftigungswahrscheinlichkeit. Die Kombination der Datensätze ermöglicht uns - unter bestimmten Annahmen - eine Identifikation kausaler Effekte von Nachbarschaftscharakteristika auf individuelles Verhalten. Wir finden einen signifikant negativen Einfluss von Arbeitslosigkeit in der Nachbarschaft auf die individuelle Beschäftigungswahrscheinlichkeit.
Keywords: J65; R23; 330; Social interactions; unemployment; neighborhood characteristics; Social interactions; unemployment; neighborhood characteristics